2016
DOI: 10.5232/ricyde2016.04305
|View full text |Cite
|
Sign up to set email alerts
|

The effects of autonomy support in physical education classes [Efectos del soporte de autonomía en clases de educación física].

Abstract: The aim of this study was to analyze the behavioral, affective and cognitive effects that an intervention based on autonomy support has in physical education classes. The sample consisted of 145 students aged between 10 and 12 (M = 10.37; SD = .68). The experimental group (n = 91) consisted of four groups (two fifth grade and two sixth) and control group (n = 54) for a fifth year and one sixth of primary education. Autonomy support, the basic psychological needs, intrinsic motivation, importance attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
(34 reference statements)
0
15
0
1
Order By: Relevance
“…The inclusion of this type of activity, among others, increased students' perception of autonomy. Similarly, after their autonomy support intervention with primary physical education teachers, Moreno-Murcia and Sánchez-Latorre [21] revealed data showing an increase in students' perception of autonomy. In this regard, Yew and Wang [64] observed clear evidence that autonomy support is necessary to achieve efficiency in physical education classes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The inclusion of this type of activity, among others, increased students' perception of autonomy. Similarly, after their autonomy support intervention with primary physical education teachers, Moreno-Murcia and Sánchez-Latorre [21] revealed data showing an increase in students' perception of autonomy. In this regard, Yew and Wang [64] observed clear evidence that autonomy support is necessary to achieve efficiency in physical education classes.…”
Section: Discussionmentioning
confidence: 94%
“…Along these lines, Ntoumanis and Standage [20] point out that a teachers' autonomy support climate positively predicts students' basic psychological needs. Other studies [21,22] show that teachers' autonomy support leads to higher perceived autonomy in students. Support of autonomy refers to those aspects that allow students develop resources to improve aspects such as internal motivation or satisfaction of their personal goals [23].…”
Section: Introductionmentioning
confidence: 93%
“…Esta taught with autonomy support. Furthermore, greater student perception of the autonomy support provided by the teacher correlated with greater classroom engagement (Cheon et al, 2012;Cheon & Reeve, 2015;De Meyer et al, 2016;Leptokaridou et al, 2014;Yew & Wang, 2016) and an intention to be active in leisure time (Chaztisarantis & Hagger, 2009: Cheon et al, 2012González-Cutre et al, 2014;Moreno-Murcia & Sánchez-Latorre, 2016;Yew & Wang, 2016). In addition, the study by Escriva- Boulley et al (2018) found that students who were taught a programme based on autonomy support improved their moderate to vigorous physical activity level.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of autonomy support teacher training, differences were also found in 62.5% of the studies in which it was implemented (Aelterman et al, 2014;Chaztisarantis & Hagger, 2009;Cheon et al, 2012;Cheon et al, 2014;Cheon & Reeve, 2015;Moreno-Murcia & Sánchez-Latorre, 2016;Perlman, 2011Perlman, , 2015Yew & Wang, 2016). While in the studies by Aelterman et al (2014) and Cheon et al (2012) training lasted six and seven hours on the same day, respectively, in the other studies it was longer, to wit nine hours over three days (three hours per day) in Chaztisarantis and Hagger (2009), a 12-hour workshop in Moreno-Murcia and Sánchez-Latorre (2016), and several weeks in Perlman (2011Perlman ( , 2013 and Yew and Wang (2016).…”
Section: Length Of Training and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation